Perluasan dan Penerapan Asas Ne Bis In Idem dalam Hukum Pidana Indonesia - Nazhif Ali Murtadho (Badan Strategi Kebijakan Hukum, 2026)
The fundamental inconsistency in the application of the principle of ne bis in idem between written regulations and judicial practice, both in litigation and non- litigation disputes, risks giving rise to repeated prosecutions that undermine the guarantee of legal certainty. This study analyzes the expansion of this principle within the framework of restorative justice in the New Criminal Procedure Code and its historical dynamics from the Colonial Criminal Code to the National Criminal Code. The method used is a type of doctrinal legal research through a statutory approach, a conceptual approach, and a case approach with a deductive legal material analysis technique. The findings indicate a terminological shift from